Ranking Of Malaysian Commercial Banks: Super-efficiency Data Envelopment Analysis (Dea) Approach - Ab Rahim, Rossazana (Asian Academy of Management (AAM), 2015)
Banking efficiency studies have tended to focus on quantifying the efficiency of financial institutions. Few attempts have been undertaken to compare the efficiency performance of domestic and foreign banks, and even fewer have compared the super-efficiency performance of both types of banks. Addressing this gap, the present study contributes to the existing literature by utilising Data Envelopment Analysis (DEA) to compute superefficiency scores for individual banks. The objectives of this study are to estimate technical efficiency and to estimate the super-efficiency index of Malaysian commercial banks over the period from 2000 until 2010. The results indicate that, in general, domestic banks perform better than foreign banks. However, the super-efficiency results reveal that individual foreign banks are more efficient than individual domestic banks